Empowering Tobacco Entrepreneurs: Marketing Management Training in Garut Regency - Isnawati, Isnawati; Herlianti, Anggun Oktavia; Setiawan, Rahyuniati; Rahmawati, Putri; Fourinta, Ananda (Fakultas Kewirausahaan Universitas Garut, 2025)
The training on marketing management for tobacco entrepreneurs in Garut Regency aimed to strengthen participants’ competencies in pricing, product differentiation, market segmentation, and digital marketing. Conducted at a central venue, the program involved entrepreneurs from multiple tobacco-producing areas and was supported by the Department of Industry and Trade (Disperindag) to enhance technical assistance and market access. A descriptive qualitative method was applied, employing in-depth interviews, focus group discussions, and participatory observation. Findings indicated a 28% average improvement in participants’ knowledge, alongside new initiatives such as adopting eco-friendly packaging and establishing collaborative marketing groups. Nevertheless, challenges were identified, including limited financial resources, resistance to innovation, and unequal internet connectivity. The participatory approach proved successful in stimulating innovation; however, sustained mentoring remains essential to ensure the long-term implementation of marketing strategies and to reinforce local economic resilience.